The Virtuous Circle: A Grounded Theory Exploration of the Good Lives Model. (December 2019) - Ryan, Miriam; McCauley, Mathew; Walsh, Davina
Sexual offenses evoke strong emotional responses and frequently elicit demands from society that offenders be indefinitely incarcerated or treated until they are deemed safe, which may impact the provision of therapeutic treatment for offenders. However, in recent years, there has been a proposal to move toward a positive, strengths-based treatment approach, namely the Good Lives Model (GLM). The present study used semi-structured interviews and a constructivist grounded theory approach to examine the experience of 13 men who were voluntarily engaging in or had completed a GLM community-based treatment program. A conceptual model emerged which outlines the process the men underwent, the factors they identified as crucial for change, and the perceived gains. The model extends previous work by exploring the process from the clients' perspective. Implications for future research, prevention, and treatment are discussed.